the study of painting in grade X SMA Negeri 4 Magelang - Rahmawati, Qoniatul (Universitas Negeri Semarang, 2017)
Painting is an popular activity on learning about arts at schools. Painting is an expression, appreciation, and recreation medium for students. Success in learning painting is determined by all learning components. . The purpose of this research was to identifying and describing the painting learning process at grade X and examines the result. The method used is descriptive research is qualitative approach, palce taken at SMA N 4 Magelang. Data collection techniques in this research based on natural conditions, primary data sources and data collection techniques such as observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and data verification. Students painting result with trees theme are, the trees were drawn was medium to big trees. Colors wich used to the stems are brown and black with green and yellow colors for the leaves. Overall views of the value of research and analysis, most of the students were able to painting watercolors but less optimizations. In the learning process, hopefully the educator be able to be more creative when choose the learning method so that the students enthusiastic and motivated at learning.